Sing or Jam? Density-Dependent Food Competition Strategies in Mexican Free-Tailed Bats (Tadarida brasiliensis) - Corcoran, Aaron J. (Frontiers in Ecology and Evolution, 2022)
Organisms compete for food in many ways, but it is often difficult to know why they use certain competition strategies over others. Bats compete for food either through aggression coupled with food-claiming signals or by actively interfering with a competitor’s sensory processing during prey pursuit (i.e., jamming). It is not known why these different behaviors are exhibited. I studied food competition between Mexican free-tailed bats (Tadarida brasiliensis) at foraging sites in Arizona and New Mexico using passive acoustic recording, insect sampling and 3-D infrared videography with or without supplemental lighting that concentrated prey. Bat activity was quantified by the number of recorded echolocation calls, while feeding behavior was indicated by feeding buzzes. Two competitive behaviors were observed—song, which was produced by bats chasing conspecifics, and sinFM calls, which jam echolocation of competitors pursuing prey. Song production was most common when few bats were present and feeding at low rates. In contrast, jamming signals were most common with many bats present and feeding at high rates. Supplemental lighting increased the numbers of bats, feeding buzzes and sinFM calls, but not song. These results indicate that bats employ different strategies—singing and chasing competitors at low bat densities but jamming competitors at high bat densities. Food claiming signals (song) may only be effective with few competitors present, whereas jamming can be effective with many bats at a foraging site. Multiple competition strategies appear to have evolved in bats that are used under different densities of competitors.